Sodium Lauryl Sulfate Increases the Efficacy of a Topical Formulation of Foscarnet against Herpes Simplex Virus Type 1 Cutaneous Lesions in Mice - Piret, Jocelyne (American Society for Microbiology (ASM), 2000)
The influence of sodium lauryl sulfate (SLS) on the efficacies of topical gel formulations of foscarnet against herpes simplex virus type 1 (HSV-1) cutaneous infection has been evaluated in mice. A single application of the gel formulation containing 3% foscarnet given 24 h postinfection exerted only a modest effect on the development of herpetic skin lesions. Of prime interest, the addition of 5% SLS to this gel formulation markedly reduced the mean lesion score. The improved efficacy of the foscarnet formulation containing SLS could be attributed to an increased penetration of the antiviral agent into the epidermis. In vitro, SLS decreased in a concentration-dependent manner the infectivities of herpesviruses for Vero cells. SLS also inhibited the HSV-1 strain F-induced cytopathic effect. Combinations of foscarnet and SLS resulted in subsynergistic to subantagonistic effects, depending on the concentration used. Foscarnet in phosphate-buffered saline decreased in a dose-dependent manner the viability of cultured human skin fibroblasts. This toxic effect was markedly decreased when foscarnet was incorporated into the polymer matrix. The presence of SLS in the gel formulations did not alter the viabilities of these cells. The use of gel formulations containing foscarnet and SLS could represent an attractive approach to the treatment of herpetic mucocutaneous lesions, especially those caused by acyclovir-resistant strains.